CRISPR genome editing to address food security and climate changes - Naglaa A, Abdallah; Hamwieh, Aladdin; Radwan, Khaled; Mahmoud, Nourhan Fouad; Baum, Michael (Taylor & Francis (Routledge), 2023)
Climate change causes an increase in the intensity of adverse abiotic and biotic stresses that could severely threaten agriculture production and food security including production, access, and prices. The world's population is anticipated to reach 9.8 billion by 2050, while food production would decline by 20%. The risk of continuous change in the environment has attracted the attention of plant scientists, who are using all available technologies to enhance crop quality and yield. Omics approaches are crucial for studying stress tolerance mechanisms and exploring candidate genes. Several efforts have been made to face these emerging challenges using traditional breeding, genetically modified organisms, and genome editing. Over the last decade, the integration of CRISPR/Cas genome editing into modern breeding programs has had a great impact on crop improvement by targeting precise changes to genomes. Genome editing is a good candidate for developing beneficial climate-resilient crops targeting biotechnological tools. Recently, new techniques in genome editing have been developed, including epigenome modifiers, and base and prime editing which are promising developments for improving plant performance and crop productivity. This chapter unravels the whole picture of the application of genome editing to address climate change and improve crops.